Cyclic oligomer design with de novo αβ‐proteins. (25th October 2017) - Lin, Yu‐Ru; Koga, Nobuyasu; Vorobiev, Sergey M.; Baker, David
Abstract: We have previously shown that monomeric globular αβ‐proteins can be designed de novo with considerable control over topology, size, and shape. In this paper, we investigate the design of cyclic homo‐oligomers from these starting points. We experimented with both keeping the original monomer backbones fixed during the cyclic docking and design process, and allowing the backbone of the monomer to conform to that of adjacent subunits in the homo‐oligomer. The latter flexible backbone protocol generated designs with shape complementarity approaching that of native homo‐oligomers, but experimental characterization showed that the fixed backbone designs were more stable and less aggregation prone. Designed C2 oligomers with β‐strand backbone interactions were structurally confirmed through x‐ray crystallography and small‐angle X‐ray scattering (SAXS). In contrast, C3‐C5 designed homo‐oligomers with primarily nonpolar residues at interfaces all formed a range of oligomeric states. Taken together, our results suggest that for homo‐oligomers formed from globular building blocks, improved structural specificity will be better achieved using monomers with increased shape complementarity and with more polar interfaces. Abstract : PDB Code(s):4PWW